Study on Strength and Energy In-take Capacity of Steel-Polyester Composite Fibre Strengthened Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
In the field of civil engineering, cement  concrete is a building material that is utilised extensively  across the board. However, there are certain worries  about its tensile strength. Many academics have  conducted study to find a remedy. Fibre strengthening is  the most effective and flexible technique to increase after crack tensile strength and energy absorption capacity.  Plain concrete was manufactured with Portland cement,  fine and coarse aggregate, flyash, silicafume, and waterreducing admixtures. Without modifying the concrete  components, steel fibre reinforced concrete specimens  with aspect ratios of 70 and 50 and volume fractions of  0.25, 0.5%, and 0.75 were constructed. Using 12mm  synthetic polyester fibres, we made 0.75, 1%, and 2%  polyester fibre reinforced concrete. Steel and polyester  fibres were mixed in volume ratios of 0.5:0.6, 0.5:0.7,  0.5:1.0, 0.5:2.0, 0.75:1.5, and 0.75:2.0 to create  composite fibre reinforced concrete samples. We used IS  516-1956 and IS 5816-1999 to test fibre-reinforced and  composite-reinforced concrete. All fibre-reinforced single  and hybrid specimens improved tensile and flexural  strength over plain concrete. Steel-polyester composite  fibres outperform single-fibre reinforced concrete because  of their synergistic impact. Schrader drop weight impact  testing was used to determine disc fracture and failure.  Each 160 mm cylinder specimen was examined using the  Brazilian method to measure its energy-intake capacity  under split tensile loading. The 120-220 mm cylinder  specimens were all compressed uniaxially. Area under  load deformation curves was drawn for each loading  conditions and those areas were used to determine the  energy In-take capacity Adding polyester, steel, or hybrid  fibre to concrete boosts its compressive strength. The  polyester/steel combination increases split tensile  strength.
Keywords: Fibre Strengthened Concrete; Plain Concrete; Composite fibre; Self-Compacting Concrete; Admixtures